Presynaptic translation: stepping out of the postsynaptic shadow - Akins, Michael R.; Berk-Rauch, Hanna E.; Fallon, Justin (Frontiers in Neural Circuits, 2009)
The ability of the nervous system to convert ephemeral experiences into enduring changes at the synapse relies upon protein synthesis. A critical subset of this synthesis occurs within the synaptic compartment itself. While local translation has been extensively characterized in the postsynaptic compartment, the potential role of presynaptic protein synthesis remains largely unexplored. Here we discuss recent advances in the study of presynaptic translation as well as the challenges confronting the field. Understanding the regulation of presynaptic function by local protein synthesis promises to shed new light on activity-dependent modification of synaptic architecture. To convert transient experiences into long-lasting structural changes at the synapse relies upon protein synthesis. It has become increasingly clear that a critical subset of this synthesis occurs within the synaptic compartment. While this process has been extensively characterized in the postsynaptic compartment, the contribution of local translation to presynaptic function remains largely unexplored. However, recent evidence highlights the potential importance of translation within the presynaptic compartment. Work in cultured neurons has shown that presynaptic translation occurs specifically at synapses undergoing long-term plasticity and may contribute to the maintenance of nascent synapses. Studies from our laboratory have demonstrated that Fragile X proteins, which regulate mRNA localization and translation, are expressed at the presynaptic apparatus. Further, mRNAs encoding presynaptic proteins traffic into axons. Regulation of synaptic release by presynaptic translation combined with modulation of response properties by postsynaptic translation provides an attractive mechanism for the local, enduring modification of synaptic structure and function. Here we review the evidence for local translation within the presynaptic apparatus and discuss potential functions for translation in this synaptic compartment.